Povstání z pokleku: Pražské bohoslužby v šedesátých letech 20. století I. - Procházková, Zora; David, Jan; Nešpor (ed.), Zdeněk R. (Lidé města, 2021)
This text provides an academic edition of the exceptional source representing (records from) observations of services in Prague Christian churches in the mid-1960s, supplemented with a contextualizing introduction and historical-religious footnotes by the editor. The specificity of the mate¬rial is that the original source takes the form of (commented) participatory observation, it is very open, and at the same time, it contains material from (almost) all existing churches and religious societies, respectively individual parishes, congregations, and places of worship in the city of Prague. Due to its length, the edition is divided into several parts; in this first part, it includes communities and services of the Unity of Brethren (Církev bratrská), the Slovak Lutheran Church (Slovenská evanjelická cirkev a.v.), the Religious Society of Czechoslovak Unitarians (Náboženská společnost československých unitářů), the Open Brethren (Křesťanské sbory), the Brotherhood of Baptists (Bratrská společnost baptistů), the Seventh-day Adventist Church (Církev adventistů sedmého dne), the Orthodox Church (Pravoslavná církev), the Evangelical Methodist Church (Evangelická církev metodistů), and the Free Reformed Church (Církev bratrská, then Jednota českobratrská).